Robot‐assisted laparoscopic (RAL) procedures in general surgery. Issue 3 (6th October 2015) - Alimoglu, Orhan; Sagiroglu, Julide; Atak, Ibrahim; Kilic, Ali; Eren, Tunc; Caliskan, Mujgan; Bas, Gurhan
Abstract: Background: Robotics was introduced in clinical practice more than two decades ago, and it has gained remarkable popularity for a wide variety of laparoscopic procedures. We report our results of robot‐assisted laparoscopic surgery (RALS) in the most commonly applied general surgical procedures. Method: Ninety seven patients underwent RALS from 2009 to 2012. Indications for RALS were cholelithiasis, gastric carcinoma, splenic tumors, colorectal carcinoma, benign colorectal diseases, non‐toxic nodular goiter and incisional hernia. Records of patients were analyzed for demographic features, intraoperative and postoperative complications and conversion to open surgery. Results: Forty six female and 51 male patients were operated and mean age was 58, 4 (range: 25‐88). Ninety three out of 97 procedures (96%) were completed robotically, 4 were converted to open surgery and there were 15 postoperative complications. There was no mortality. Conclusion: Wide variety of procedures of general surgery can be managed safely and effectively by RALS. Copyright © 2015 John Wiley & Sons, Ltd.